Association Between Maternal and Fetal TLR4 (896A>G, 1196C>T) Gene Polymorphisms and the Risk of Pre‐term Birth in the Polish Population. (7th January 2013) - Bitner, Adam; Sobala, Wojciech; Kalinka, Jarosław
<x xml:space="preserve">Abstract</x> Problem Bacteria activates Toll‐like receptor 4 on immune system cells leading to preterm birth (PTB). The aim of study was to evaluate the impact of maternal and fetal carriage of TLR4 gene polymorphisms on the risk of PTB. Method of Study Frequency of TLR4 (896A>G, 1196C>T) variants was determined in 121 women who delivered preterm, 152 women who delivered at term, 49 term newborns and 35 preterm newborns with the use of PCR‐RFLP. Results We found no associations between frequency of TLR4 polymorphic alleles in mothers and fetuses and the risk of delivery before 37th week of pregnancy. However significantly lower frequency of TLR4 1196T allele was observed in subgroup of mothers who delivered before 33rd week comparing with those who delivered later (4, 4% versus 14, 2%, OR = 0, 28 (95%CI: 0, 04–0, 99). Conclusions Maternal carriage of TLR4 1196T allele may be associated with reduced risk of PTB before 33rd week of gestation in Polish population.